Preparation of pH-Responsive Tanshinone IIA-Loaded Calcium Alginate Nanoparticles and Their Anticancer Mechanisms - Tianying Ren; Jing Wang; Yingxin Ma; Yichen Huang; Somy Yoon; Lijun Mu; Ru Li; Xuekun Wang; Lina Zhang; Pan Li; Lusha Ji (Pharmaceutics)
Background: Tanshinone IIA (Tan IIA) is a lipophilic active constituent derived from the rhizomes and roots of Salvia miltiorrhiza Bunge (Danshen), a common Chinese medicinal herb. However, clinical applications of Tan IIA are limited due to its poor solubility in water. Methods: To overcome this limitation, we developed a calcium alginate hydrogel (CA) as a hydrophilic carrier for Tan IIA, which significantly improved its solubility. We also prepared nanoparticles with pH-responsive properties to explore their potential for controlled drug delivery. The physicochemical properties of Tan IIA/CA nanoparticles were evaluated, including their size, stability, and release profile. We also utilized RNA sequencing to further investigate the underlying anticancer mechanisms of Tan IIA/CA nanoparticles. Results: The Tan IIA/CA nanoparticles demonstrated enhanced solubility and exhibited potent anticancer activity in vitro. Additionally, the nanoparticles showed promising pH-responsive behavior, which is beneficial for controlled release applications. Further investigation into the molecular mechanisms revealed that the anticancer effects of Tan IIA/CA were mediated through apoptosis, ferroptosis, and autophagy pathways. Conclusions: This study confirms the anticancer potential and mechanisms of Tan IIA, while also presenting an innovative approach to enhance the solubility of this poorly soluble compound. The use of CA-based nanoparticles could be a valuable strategy for improving the therapeutic efficacy of Tan IIA in cancer treatment.